A node‐localized transporter OsZIP3 is responsible for the preferential distribution of Zn to developing tissues in rice. (October 2015) - Sasaki, Akimasa; Yamaji, Naoki; Mitani‐Ueno, Namiki; Kashino, Miho; Ma, Jian Feng
Summary Developing tissues such as meristem with low transpiration require high Zn levels for their active growth, but the molecular mechanisms underlying the preferential distribution to these tissues are poorly understood. We found that a member of the ZIP (ZRT, IRT‐like protein), OsZIP3, showed high expression in the nodes of rice (Oryza sativa). Immunostaining revealed that OsZIP3 was localized at the xylem intervening parenchyma cells and xylem transfer cells of the enlarged vascular bundle in both basal and upper nodes. Neither OsZIP3 gene expression nor encoded protein was affected by either deficiency or toxic levels of Zn. Knockdown of OsZIP3 resulted in significantly reduced Zn levels in the shoot basal region containing the shoot meristem and elongating zone, but increased Zn levels in the transpiration flow. A short‐term experiment with the 67Zn stable isotope showed that more Zn was distributed to the lower leaves, but less to the shoot elongating zone and nodes in the knockdown lines compared with the wild‐type rice at both the vegetative and reproductive growth stages. Taken together, OsZIP3 located in the node is responsible for unloading Zn from the xylem of enlarged vascular bundles, which is the first step for preferential distribution of Zn to the developing tissues in rice.